Comparative Analysis of American and Indonesian Democracies: A Literature Review - Agussalim Burhanuddin (Journal of Society and Governance, 2017)
United States of America and Indonesia have been claimed as two of democratic countries in the world. While Indonesian democracy is considered relatively new, it poses a promising commitment of a full-fledged democracy. The long-time established American political system, on the other hand, has not yet achieved a satisfactory model of democracy. This article aims to observe the strength and the weaknesses of the two democracies using literature reviews in a comparative approach. It is revealed that American and Indonesian democracies still have a long way to become a perfect model of political system. Keywords: Democracy, American democracy, Indonesian democracy.